Catalytic Co-Pyrolysis of Low Rank Coal and Sewage Sludge Blends : An Insight into Kinetic, Synergetic and Thermodynamic Parameters - Muhammad Rabah (00000329779); Dr Abeera Ayaz Ansari (USPCAS-E, NUST, Islamabad, 2022)
TH-446
Keywords: MS-ESE Thesis MS Thesis